Altered Spontaneous Brain Activity in Betel Quid Dependence Chewers: A Resting-State Functional MRI Study With Percent Amplitude of Fluctuation - Fu, Lili; Chen, Huijuan; Liu, Tao; Liu, Liting; Fu, Qingqing; Huang, Weiyuan; Chen, Feng (Frontiers in Psychiatry, 2022)
Objective: This study aimed to investigate brain spontaneous neural activity changes in betel quid (BQ) chewers using the percent amplitude of fluctuation (PerAF) method. Methods: 48 betel quid-dependent (BQD) chewers were included in this study. 35 age-, gender- and education level-matched volunteers were recruited as the healthy control (HC) group. All subjects underwent resting functional magnetic resonance imaging (rs-fMRI) and neuropsychological tests. PerAF method was applied to identify BQD-related regional brain activity alterations. Independent samples t-test was used to evaluate PerAF difference across two groups. Spearman correlation analysis was performed to investigate the association between PerAF changes and clinical features, including BQD scores, illness duration, Hamilton Depression Rating Scale-24item(HAMD-24), and Hamilton Anxiety Rating Scale-14 item(HAMA-14). Results: Compared to the control group, BQD chewers showed decreased PerAF in the right anterior cingulate cortex (ACC), right middle frontal gyrus (MFG), right insula, right precuneus, left putamen, left SupraMarginal gyrus(SFG), left cerebellum as well as increased PerAF in right orbitofrontal, left superior temporal gyrus (STG) ( p < 0.05, Gaussian random field (GRF) corrected). PerAF values of the right MFG, the right ACC showed a negative correlation with the duration of BQD ( p < 0.05). Conclusion: Our findings suggested that betel quid chewing is associated with spontaneous neural activity alterations in the impulsivity areas (MFG and ACC ), cognitive (MFG, ACC, precuneus and the cerebellum), and reward (orbitofrontal, putamen and insula) systems, which may be correlated with neuropathological mechanisms of BQD. Also, PerAF may be useful as a potential sensitive biomarker for identifying spontaneous brain activity alterations in individuals with BQD.